Intradermal versus subcutaneous immunization: Effects of administration route using a lipid-PLGA hybrid nanoparticle tuberculosis vaccine - Szachniewicz, M.M.; van den Eeden, S.J.F.; van Meijgaarden, K.E.; Franken, K.L.M.C.; van Veen, S.; Geluk, A.; Bouwstra, J.A.; Ottenhoff, T.H.M. (European journal of pharmaceutical sciences, 2025)
Tuberculosis (TB) remains a significant global health challenge, latently affecting around a quarter of the global population. The sole licensed TB vaccine, Mycobacterium bovis Bacillus Calmette-Guérin (BCG), shows variable efficacy, particularly among adolescents and adults, underscoring the pressing need for more effective vaccination strategies. The administration route is crucial for vaccine efficacy, and administration via the skin, being rich in immune cells, may offer advantages over conventional subcutaneous routes, which lack direct access to abundant antigen-presenting cells. This study compared the immunogenic effects of intradermal versus subcutaneous administration of a candidate TB vaccine delivering a Ag85B-ESAT6-Rv2034 (AER) multiphase fusion recombinant protein, in lipid-poly(D,L-lactic-co-glycolic acid) (lipid-PLGA) nanoparticles in mice. In-depth evaluation of immune responses in splenocytes was performed using 27-marker spectral flow cytometry. Both routes elicited significant T-cell responses. However, intradermal administration uniquely increased polyfunctional CD4+ and CD8+ T-cells producing IL-2, IFNγ, and TNFα, associated with protection against TB. Additionally, it significantly increased CD69+ B-cell counts and induced higher AER-specific antibody titers, particularly IgG2a. These results underscore the superior immunogenic potential of intradermal vaccine administration by effectively inducing immune cells associated with TB protection, highlighting its significance in the development of new vaccine strategies. [Display omitted]